Atmospheric corrosion map of structural steel in industrial area: a preliminary investigation. (August 2019) - Huzni, S; Affandi,; Tanjung, I; Fonna, S
Abstract: This paper explains the results of the initial stage of investigation of atmospheric corrosion on structural steel in industrial zones. Investigation is carried out on two shape profile of low carbon steel that is widely used for the construction of structures, namely sheet, and elbow. Corrosion rate measurement process and preparation were carried out based on ASTM G-50 and ASTM G-1 standards, with a total exposure time of six months in Medan Deli District, Medan, North Sumatra. The results of this initial stage of the investigation show that the average corrosion rate of low carbon steel for each profile is different, but overall it is still in the "good" category. This investigation will be continued for up to twelve months to obtain more complete data.